(untitled) (Research, Society and Development, 2021)
Objectives: to compare vocal parameteres between honest and lying speech. Methods: 40 subjects (20 men and 20 women), with ages between 19 and 58 years, were submitted to tests of honest and lying speeches. To acoustic analyses, the sustainted vowel /ae/ with habitual frequency and intensity of voice were requested before the test and in the test. Voice and speech samples were captured by microfone and vídeo records The vocal parameteres analysed were fundamental frequency (f0), pitch, loudness, phonatory tension, instability and vocal attack. Results: the vocal parameteres of tension (p=0,004) and vocal attack (p=0,01) demonstrated estatistically significant diferences. The loudness demonstrated a tendency to increase in lying speech (p=0,08). Conclusion: the vocal parameteres of tension and vocal attack seems to differenciate between honest and lying speech, which may suggest a possible change in vocal behavior on lying speeches.